A Psychoanalytical Perspective of Patterson’s Kiss the Girls - Verma, Sumit Raj (Patan Pragya, 2023)
Kiss the Girls is a riddle/ suspenser tale of compulsive hijacking and murder. Casanova, a periodical killer and kidnapper, has killed several women in the vicinity of the University of North Carolina. In addition to the girls that have been killed, several others are missing. Among the missing girls is the bastard of famed operative Alex Cross. Cross, through his connections at the FBI, is allowed to work on the case. The killer seems to have a taste for extremely beautiful women and is known for his near perfect crimes. Casanova stalks his prey with great care and attention to detail. His most recent victim is Dr. Kate McTiernan, with whom Casanova came, fixated because of her stunning aesthetics and great intelligence. He holds her interned, along with several of his other victims, in an underground nest in the forestland. Casanova is uncommunicative, always wearing a mask when he meets his girls. Stewing death for breaking the house rules, Kate breaks free and returns to civilization. Kate recounts the odd miracle that the house of the killer faded after she exited. Kate and Cross meet and get fast musketeers.